Development of objective test functions for modeling and sensitivity analysis of the mechanical behaviour of aluminum-agro-marine waste composites - Obinna Onyebuchi Barah; Stephen Ndubuisi Nnamchi; Milon Dennison Selvam; Mustafah Muhamad Mundu; Abubakar Abdulkarim (Materials Research Express)
Aluminum-based composites reinforced with agro-marine waste materials present an eco-friendly, cost-effective solution for industries needing lightweight and durable materials. This study develops and evaluates the mechanical properties of aluminum (AA6061) composites reinforced with plantain stem ash, eucalyptus wood ash, and periwinkle shell powder for potential aerospace, automotive, and marine applications. Composite samples were prepared according to ASTM standards for tensile, compressive, flexural, wear, and fatigue tests. Objective Test Functions (OTFs) were derived using physical modeling and sensitivity analysis to filter impactful variables. Testing was conducted using universal testing machines, and wear/friction tests followed ASTM G99 guidelines. The physical models showed strong correlations (adjusted R ^2 : 0.9033–1.0000). Measured properties included tensile strength (1907.46–2000.05 Pa), compressive strength (30.33–215.14 Pa), flexural strength (412.72–556.42 N-m ^2 ), wear rate (55.01–63.27 m ^3 /m), coefficient of friction (0.102), and fatigue cycle (13.81–27.63 cycles). Except for the coefficient of friction, all results were consistent with the developed OTFs, confirming the material’s structural integrity. The composites displayed favourable properties for use in aerospace, automotive, and marine industries, offering strength, lightweight characteristics, and corrosion resistance. The OTFs validated the material’s performance, making it a viable alternative to conventional materials. Consequently, aluminum-agro-marine waste composites demonstrate excellent mechanical properties, with high potential for industrial applications.